All-solid-state lithium-ion and lithium metal batteries – paving the way to large-scale production - Schnell, Joscha; Günther, Till; Knoche, Thomas; Vieider, Christoph; Köhler, Larissa; Just, Alexander; Keller, Marlou; Passerini, Stefano; Reinhart, Gunther (Journal of power sources, 2018)
Challenges and requirements for the large-scale production of all-solid-state lithium-ion and lithium metal batteries are herein evaluated via workshops with experts from renowned research institutes, material suppliers, and automotive manufacturers. Aiming to bridge the gap between materials research and industrial mass production, possible solutions for the production chains of sulfide and oxide based all-solid-state batteries from electrode fabrication to cell assembly and quality control are presented. Based on these findings, a detailed comparison of the production processes for a sulfide based all-solid-state battery with conventional lithium-ion cell production is given, showing that processes for composite electrode fabrication can be adapted with some effort, while the fabrication of the solid electrolyte separator layer and the integration of a lithium metal anode will require completely new processes. This work identifies the major steps towards mass production of all-solid-state batteries, giving insight into promising manufacturing technologies and helping stakeholders, such as machine engineering, cell producers, and original equipment manufacturers, to plan the next steps towards safer batteries with increased storage capacity. [Display omitted] •Requirements for industrial production of solid-state batteries are investigated.•Process chains for electrode fabrication and cell assembly are presented.•A detailed comparison with conventional lithium-ion cell production is given.•Guidelines for stakeholders in the scale-up of fabrication are provided.